2019
DOI: 10.2174/1570162x17666190919115036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Different Genotypes of HIV-1 in Injection Drug Users in China: A Systematic Review and Meta-Analysis

Abstract: Background: Since 1981, an increasing trend in HIV has been observed for transmission via injection drug users (IDUs), sexual transmission and mother-to-child transmission. The IDUs are blamed for early increases in HIV-positive cases in China. Objective: HIV genotypes of IDUs were comprehensively analysed to trace the source and relationships of the AIDS epidemic in China. Methods: Relevant databases written in English and Chinese were searched. Overall, 7,149 publications were identified in six databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Moreover, PDR transmission and the DRM sharing patterns within networks in this region were both associated with the CRF08_BC subtype. Previous studies have found that CRF08_BC was one of the primary drivers of HIV-1 infection among IDUs, especially in Southwest China (He et al, 2012;Jiang et al, 2019). Frequent needle exchange and poor ART adherence among IDUs could lead to a higher risk of drug-resistant strains spreading in this population (Bangsberg et al, 2007;Thanh et al, 2009;Muyldermans and Sasse, 2014;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, PDR transmission and the DRM sharing patterns within networks in this region were both associated with the CRF08_BC subtype. Previous studies have found that CRF08_BC was one of the primary drivers of HIV-1 infection among IDUs, especially in Southwest China (He et al, 2012;Jiang et al, 2019). Frequent needle exchange and poor ART adherence among IDUs could lead to a higher risk of drug-resistant strains spreading in this population (Bangsberg et al, 2007;Thanh et al, 2009;Muyldermans and Sasse, 2014;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Several HIV-1 subtypes were heterogeneously distributed in China. The dominant circulating subtypes were CRF01_AE and CRF07_BC, followed by CRF08_BC, subtype B, and CRF55_01B [10][11][12][13]. Previous studies have shown that HIV-1 genetic diversity in China, especially clades BC and AE, were likely to impact the quantitation of VL using different assays [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, CRF08_BC originated in Yunnan Province and was prevalent among both IDUs and heterosexuals [ 56 , 57 ]. In this study, approximately 40.0% of CRF08_BC in Qinzhou occurred among IDUs with a predominantly YM population, and the risk of transmission was high [ 58 , 59 ]. Therefore, CRF08_BC is easily transmitted from the YM population to other subpopulations.…”
Section: Discussionmentioning
confidence: 99%